Optimal design of sustainably efficient biorefineries supply chain - Machin Ferrero, Lucas M. (2023)
A more comprehensive use of biomass as raw material to produce food, energy and products would result in an important contribution towards the Sustainable Development Goals. The concept of biorefinery allows regions with abundant natural resources to make the most of available biomass for these purposes, achieving progressive independence from fossil resources. This study presents a framework for the multi-criteria design of biorefinery supply chains (SC) under sustainability considerations. Therefore, an optimization approach of different scenarios is performed followed by a ranking based on the Data Envelopment Analysis (DEA) model to assess the efficiency according to different economic, environmental and social indicators. The capabilities of this approach are demonstrated through a case study of the biomass SC centered in the Northwest of Argentina.